2022
DOI: 10.3389/fpsyt.2021.792838
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of General Health Questionnaire-12 in Chinese Dental Healthcare Workers During the COVID-19 Pandemic

Abstract: BackgroundThe General Health Questionnaire-12 (GHQ-12) is a widely used instrument to assess mental health status. However, little is known about its applicability in Chinese healthcare workers. This study aimed to evaluate the reliability and validity of the GHQ-12 in Chinese dental healthcare workers.MethodsDental healthcare workers participated in the first occupational survey in China conducted by the Chongqing Stomatological Association from February 2021 to March 2021 by filling out GHQ-12. The reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A factor score is calculated by adding the item score, and values span 0–12, with higher scores indicating poorer mental health. The GHQ-12 has demonstrated both convergent validity ( r = 0.47–0.76, p < 0.05) and internal consistency (Cronbach’s α = 0.89) ( Zhong et al, 2021 ). Cronbach’s alpha coefficient for GHQ-12 was 0.85 in the present sample.…”
Section: Methodsmentioning
confidence: 99%
“…A factor score is calculated by adding the item score, and values span 0–12, with higher scores indicating poorer mental health. The GHQ-12 has demonstrated both convergent validity ( r = 0.47–0.76, p < 0.05) and internal consistency (Cronbach’s α = 0.89) ( Zhong et al, 2021 ). Cronbach’s alpha coefficient for GHQ-12 was 0.85 in the present sample.…”
Section: Methodsmentioning
confidence: 99%
“…The second part was the Chinese version of the General Health Questionnaire, composed of 12 items. It is widely used to assess mental health status (Zhong et al, 2021), and has also been successfully applied to Chinese civil servants, adolescents, and university students (Li et al, 2009;Ye, 2009;Liang et al, 2016). Each item is used to obtain a dichotomous score based on a conventional bimodal scoring method (0-0-1-1), rated on a 4point scale.…”
Section: Survey Questionnairementioning
confidence: 99%
“…Since the beginning of the pandemic, this is the first attempt to develop a validated instrument to wholistically assess the impact of COVID‐19 responses on healthcare providers in the Nigerian population. Previous tools that assessed the impacts of the pandemic either narrowed their scopes to psychological impacts on the general population (Kalanidhi et al, 2021 ), or sampled healthcare providers from other regions who shared different sociocultural background from Nigeria (Talaee et al, 2022 ; Zhong et al, 2021 ). Nigeria as a low income country is threatened by various infrastructural inadequacies.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies also support this finding. Earlier study that assessed the validity and reliability of general health questionnaire on Chinese healthcare workers during COVID‐19 found the Cronbach's alpha coefficient as 0.892 (Zhong et al, 2021 ). Similarly, a study that validated the fear of COVID‐19 scale (Ahorsu et al, 2020 ) and two other separate studies that respectively evaluated the validities and reliabilities of the tools for assessment of physical and psychological impacts of COVID‐19 (de Sá‐Caputo et al, 2020 ) and stress and burnout in healthcare workers during COVID‐19 pandemic (Talaee et al, 2022 ) reported a similar range of Cronbach's alpha coefficients of 0.80 to 0.89.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation